The Effect of Electronic Flashcards on EFL Students' Vocabulary Learning: The Case of Saudi Arabia - Asma A. Alghamdi; Tariq Elyas (RIRAI Publisher, 2020)
This study aimed to investigate the effect of electronic flashcards on EFL vocabulary learning of preparatory-year female students at a Saudi Arabia. It was conducted following the quantitative research methodology with a quasi-experimental design. Two groups were assigned: an experimental group who used electronic flashcards, and a control group who employed the traditional method of vocabulary learning. A pre-test and a post-test were administered in order to appraise their performance before and after the experiment. The results revealed that the post-test scores of students in the experimental group were significantly higher than their pre-test. Also, the results showed that electronic flashcards promoted students' vocabulary, causing a statistical significance in comparison to the control group. Based on these findings, this study was able to draw a number of implications and recommendations